Effects of donor age on human adipose-derived adherent stromal cells under oxidative stress conditions. Issue 3 (March 2018) - Kim, Sang Woo; Choi, Jung-Won; Lee, Chang Youn; Lee, Jiyun; Shin, Sunhye; Lim, Soyeon; Lee, Seahyoung; Kim, Il-Kwon; Lee, Hoon-Bum; Hwang, Ki-Chul
Objective: Adipose-derived stromal vascular fractions (SVFs) are heterogeneous complex populations of cells with therapeutic efficacy for tissue generation and vascular stabilization. SVFs have cardiomyogenic potential, and many researchers have examined the possibility of SVF transplantation for heart disease. In cell-based therapies, donor age affects the regenerative capability, cell yield, and differentiation potential of adult tissues; however, opposing or controversial results have been found in humans. We examined whether SVF transplantation into impaired heart tissue shows differential effects according to donor age. Methods: We investigated differences in protein expression in human umbilical vein endothelial cells (HUVECs) co-cultured with adipose-derived adherent stromal cells (ADASs) from donors of different ages [>40-year-olds (40s group) and >60-year-olds (60s group)] under oxidative stress conditions. Results: Although co-culturing HUVECs with ADASs ameliorated inflammation due to increased oxidative stress conditions, few differences were observed between the ADASs from the 40s and 60s groups. Moreover, the Database for Annotation, Visualization, and Integrated Discovery classification tool revealed differentially expressed genes in the Kyoto Encyclopedia of Genes and Genomes pathway associated with cytokine–cytokine receptor interaction in response to ADASs. Conclusion: Protein expression profiles were unchanged in HUVECs induced by isolated ADASs from donors of different ages under oxidative stress conditions.